Comparing Raman mapping and electron microscopy for characterizing compositional gradients in thermoelectric materials. (1st April 2020) - Yasseri, Mohammad; Schüpfer, Dominique; Weinhold, Marcel; Chen, Limei; Kamila, Hasbuna; Müller, Eckhard; de Boor, Johannes; Klar, Peter J.
Abstract: We demonstrate that Raman mapping provides a cheap, fast, and non-invasive way of mapping compositional fluctuations occurring in state-of-the-art thermoelectric materials. Exemplarily, we discuss Raman results obtained on an Mg2 Si–Mg2 Sn diffusion couple and compare resulting compositional mappings with those obtained on the same sample using electron microscopy in conjunction with energy-dispersive X-ray emission and back-scattered electrons as probes. We obtained the same level of quantitative information by the three approaches. The lateral resolution achieved in the Raman mappings can be as good as 1.4 µm and typical recording times per data point are of the order of 50 s. Graphical abstract: Image, graphical abstract